Answer:
well if the bottom two are 30 then that leaves you with 70
Step-by-step explanation:
The first equation gives:
y = 2 * (x + 3) >>> y = 2x + 6
Or
2x - y = -6
The second sentence gives:
y = 5 + 3x >>> 3x - y = -5
The answer is (A), the first choice.
I this the answer you are looking for would probably be 47.7%.
hope this helps!!
Answer: -1
Step-by-step explanation: First, factor out 3.6. You should get -m+3. Since the coefficient is just the number being multiplied to the variable (which is m here), your coefficient should be -1 because m is being multiplied to -1 to make -m. Hope this helps!